Attribute Perception Mapping Services Domestic Airlines Using Correspondence Analysis - Riandarini, Reni Heviandri; Sumarwan, Ujang; Kirbrandoko, Kirbrandoko; Noor, Lilik (International Research Journal of Business Studies, 2015)
Positioning analysis provides a better understanding of the position based on the perception of passenger flights to service these attributes attached to each airline. This study aims to perform positioning of the domestic airline services based attributes, which characterize the airline based on the perception of consumers. Correspondence Analysis (CA) is used to determine the positioning of the six commercial airlines in Indonesia. The results of correspondence analysis showed that the airline Garuda, Lion Air, Citilink and Air Asia already has its own characteristics inherent in the minds of consumers, while the two other airlines, namely Batik Air and Sriwijaya Air has not had a special identifier.